KONTEKSTUALISASI KONSEP JODOH, SAKINAH, MAWADAH, WARAHMAH DALAM AL-QUR’AN - Fawait Syaiful Rahman (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
Abstract Islam limits the pattern of interaction between men and women outside of marriage so that their respective honor can be maintained. In humans, there is a tendency of animal tendencies that have the potential to lead to prohibited cases (mungkarat or muharramat). Islam also regulates the provisions if a man and woman want a halal relationship as well as a reward value in the framework of marriage. An ideal marriage is generally defined as a marriage that is the result of one's own choice without any outside intervention, the two partners are never heard of fighting and arguing, and a married couple is supported by an established economy, such family conditions are considered ideal families. After several weeks or more, the news was heard that the husband and wife were divorced, even though at the beginning of the marriage they had received a prayer